Efektivitas Program Kredit Usaha Rakyat (KUR) Syariah PT. Pegadaian untuk Pengembangan Usaha Mikro Kecil Menengah - Firdaus, Rifqi; Makhtum , Ahmad (Ulumuna: Jurnal Studi Keilsman, 2023)
This study aims to analyze the effectiveness and impact felt by MSME actors in realizing the sharia KUR program and whether it is really able to provide benefits to the sustainability of the businesses they have. The research method used by the author is descriptive-qualitative research. Through descriptive research, researchers will try to describe the phenomenon regarding the effectiveness of the Sharia People's Business Credit (KUR) program of PT Pegadaian for the development of micro, small, and medium enterprises. The results of this study state that the presence of KUR credit Sharia Pegadaian Blega Branch in the community is very helpful for business people to get alternative capital. The benefits obtained with credit are for business development and financial management, which are easier to rotate. The results of the interviews conducted said that loans from pawnshops are not only used to increase business capital but also for daily living expenses and even to help finance children who are st